Media Pembelajaran berbasis Teknologi sebagai Inovasi Pendidikan Karakter Aswaja di Era Revolusi Industri 4.0 - Nudin, Ikhwan (Universitas Islam Malang, 2023)
The era of the industrial revolution 4.0 is an era where almost everything is controlled by technology, including in the world of education. This technology-based learning media facilitates the learning process in terms of effectiveness and efficiency. There are several technology-based learning media that can be used to support the learning process. These media include Audio Media, Visual Media, and Audio Visual Media. This research seeks to demonstrate innovation in aswaja character education in the era of the industrial revolution 4.0 by using technology-based learning media. This study uses the content analysis method, which is a research method that utilizes a set of procedures to draw valid conclusions from books and documents. This learning media can be implemented in all existing materials, especially Aswaja. In addition, it can be implemented at all levels of education, of course teachers are required to continue to innovate with the learning media that will be used. Many benefits can be felt with the existence of technology-based learning media, besides being able to attract students' learning interest it can also improve learning achievement results. Therefore, technology-based learning media is expected to be used in the learning process.